RESPONSABILIDADE SOCIOAMBIENTAL NO SETOR SUCROALCOOLEIRO - Freitas, Simone Muniz Teixeira de (2006)
The sugarcane agro industrial sector; a major cane, sugar and alcohol (ethanol) producer; generates jobs, increases trade, including trading opportunities in international markets, as well as it open new paths in the energy generation sector, making it possible to companies in this sector to exchange their experiences in the field. Nowadays the alcohol (ethanol) is recognized worldwide for its social, environmental and economic advantages, particularly by the developed nations that are interested in the technologies developed so far in Brazil. This study major objective was to do a survey in order to better understand and characterize the sugarcane agro industrial sector, finding out the sugarcane industries that looking for international market possibilities incorporated social and environmental responsibility in their management system. Nowadays, in order to avoid commercial barriers, certification labels are being considered a pre requisite to the majority of industries in different fields to enter in international markets. This study evaluated a possible socio environmental certificate for the sugar cane agro industrial sector, as technological innovations and the socio environmental risks come in parallel. Through an exploratory research, this study verified that the existent certifications in the sugar mills and in the alcohol (ethanol) industry are not many and that they are in majority related to Quality Management System and more recently to Environmental Management System, particularly in São Paulo State. This study concluded that the sector in experiencing a transition phase; is going through major changes and contradictions since its introduction in Brazil in the begging of its history. In addition, the sugar cane production is linked to a sector of great interests in the national and in the international markets, being an example of good and bad experiences for the Brazilian nation. Even though, the sugar cane sector is major contributor to the nation to achieve a sustainable development as it supplies clean and renewable energy, regarding ethanol fuel as well as energy co-generation.